Kepuasan Kerja sebagai Variabel Intervening pada pengaruh Kepemimpinan Terhadap Kinerja Pegawai - Muslih Muslih; Muhammad Didit Pratama (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
The purpose of this study was to determine and analyze the influence of leadership on employee performance through job satisfaction at PT. Perkebunan Nusantara IV (Persero) Medan directly or indirectly. The approach used in this study is a causal approach. The population in this study were all employees of PT. Perkebunan Nusantara IV (Persero) Medan. The sample in this study using the slovin formula totaling 81 employees of PT. Perkebunan Nusantara IV (Persero) Medan. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. The data processing in this study uses the PLS (Partial Least Square) software program. The results of this study prove that directly leadership and job satisfaction have a significant effect on employee performance and indirectly leadership has a significant effect on employee performance. Through job satisfaction at PT. Perkebunan Nusantara IV (Persero) Medan.